Creating safer health systems: Lessons from other sectors and an account of an application in the Safer Clinical Systems programme. (May 2017) - Spurgeon, Peter; Flanagan, Hugh; Cooke, Matthew; Sujan, Mark; Cross, Stephen; Jarvis, Rose
Despite well meaning initiatives over decades, the percentage of inpatients suffering adverse events remains constant in most advanced health systems. The notion of incident reporting as used in other safety critical industries has proved far less effective in healthcare. This article describes a new patient safety paradigm in the search for improved patient safety in healthcare. Underpinned by a holistic use of human factors the Safer Clinical Systems programme involves a proactive, risk-based approach seeking to eliminate or control risk before it is converted to patient harm. The tools and techniques applied by healthcare professional in real-life settings are described along with the outcomes of a significant reduction in risk and improvement in safety culture as measured by the Safety Culture Index. The challenges of applying the approach are discussed but it is argued that important progress could be made if a critical mass of healthcare staff were helped to acquire skills in human factors.